Reconfigurable fault-tolerant attitude control for over-actuated hypersonic flight vehicle with actuator failures - Li, Ao; Hu, Xiaoxiang; Dong, Kejun; Li, Hongzeng; Xiao, Bing (Alexandria engineering journal, 2025)
This paper proposes a novel fast attitude fault-tolerant control (FTC) scheme for over-actuated hypersonic flight vehicles experiencing actuator failures, such as stuck faults and loss of effectiveness faults. The FTC scheme comprises two main components: a systematic algorithm in the control layer and a control allocation method in the reconfiguration layer, working together to achieve fault tolerance. Drawing inspiration from model predictive static programming, a step-by-step algorithm is developed to quickly resolve control torque under fault conditions, ensuring prescribed tracking performance. The vehicle system's coupling and uncertain disturbances are treated as total disturbance and estimated in real-time using an extended state observer. In the reconfiguration layer, a pseudo-inverse-based control allocation method is utilized to distribute the desired control torque across redundant rudder actuators. The proposed FTC scheme is applied to a hypersonic flight vehicle system subject to stuck faults, loss of effectiveness faults, modeling errors, and external disturbances. Simulation results are presented to demonstrate the superiority and effectiveness of the proposed FTC scheme. Owing to its fast computational speed, the scheme holds potential for online implementation, enabling rapid reconstruction of aerodynamic rudder actuators during failures.